Pengaruh Occupational Stress Dan Job Embeddedness Terhadap Employee Life Satisfaction pada PT Wahana Express di Karanganyar - Gabriel Meisa Wijayanto; Nike Larasati (Jurnal Visi Manajemen, 2025)
The purpose of this study was to determine the effect of occupational stress, job embeddedness on employee life satisfaction at PT Wahana Exspress in Karanganyar. The population in this study were employees of PT Wahana Prestasi Logistik, totaling 120 employees. The sampling technique was purposive sampling technique.. Purposive sampling is a technique for determining samples with certain considerations, so that the sample in this study was 84 respondents. Data collection techniques using questionnaires, literature study and observation. Data analysis using instrument test, classical assumption test, descriptive analysis, instrument test, multiple linear regression test, t test, F test and coefficient of determination test. The t test results show that occupational stress has a significant and negative effect on employee life satisfaction at PT Wahana Express in Karanganyar, it is proven to be true, and job embeddeness has a significant and positive effect on employee life satisfaction at PT Wahana Express in Karanganyar, it is proven to be true. The results of the F test in this study have a calculated F value of 213.584 with a significance value (p.value) of 0.000 <0.05. The test result of the coefficient of determination (R²) for this model is 0.837 or 83.7%.